Zinc excess impairs Mycobacterium bovis growth through triggering a Zur-IdeR-iron homeostasis signal pathway - Xiaohui Li; Liu Chen; Yuankun Wang; Xiao Guo; Zheng-Guo He (Microbiology Spectrum, 2023)
ABSTRACT Zinc excess is toxic to bacteria and, thus, represents an important innate defense mechanism of host cells, especially against mycobacterial infections. However, the signaling pathway triggered by zinc excess and its relationship with iron homeostasis remain poorly understood in mycobacteria. Here, we characterize a novel Zur-IdeR-iron homeostasis signaling pathway that modulates the growth of Mycobacterium bovis under zinc toxicity. We found that the regulator Zur interacts with the iron-homeostasis regulator IdeR, enhancing the DNA-binding ability of IdeR. Excess zinc disrupts this interaction and represses ideR transcription through Zur, which promotes the expression of iron uptake genes and leads to the accumulation of intracellular iron in M. bovis. The elevated iron levels lower the bacterial survival ability under excess zinc stress. Consistently, deleting zur hinders intracellular iron accumulation of M. bovis and enhances bacterial growth under stress, while silencing ideR impairs the growth of the wild-type and zur-deleted strains under the same conditions. Interestingly, both Zur and IdeR are conserved in bacteria facing zinc toxicity. Overall, our work uncovers a novel antimicrobial signal pathway whereby zinc excess disrupts iron homeostasis, which may deepen our understanding of the crosstalk mechanism between iron and zinc homeostasis in bacteria. IMPORTANCE As a catalytic and structural cofactor of proteins, zinc is essential for almost all living organisms. However, zinc excess is toxic and represents a vital innate immunity strategy of macrophages to combat intracellular pathogens, especially against mycobacterial pathogens such as Mycobacterium tuberculosis, the causative agent of tuberculosis. Here, we first characterize an antibacterial signaling pathway of zinc excess and its relationship with iron homeostasis in M. bovis. We found that excess zinc inhibits the transcription of ideR and its DNA-binding activity through Zur, which, in turn, promotes the expression of iron uptake genes, causes intracellular iron accumulation, and finally impairs the bacterial growth. This study reveals the existence of the Zur-IdeR-iron homeostasis pathway triggered by zinc excess in M. bovis, which will shed light on the crosstalk mechanisms between zinc and iron homeostasis in bacteria and the antimicrobial mechanisms of host-mediated zinc toxicity.